Biochemically Controlled Release of Dexamethasone Covalently Bound to PEDOT. Issue 41 (25th June 2018) - Carli, Stefano; Trapella, Claudio; Armirotti, Andrea; Fantinati, Anna; Ottonello, Giuliana; Scarpellini, Alice; Prato, Mirko; Fadiga, Luciano; Ricci, Davide
Abstract: PEDOT (Poly(3, 4‐ethylenedioxythiophene)) is one of the most promising electrode materials for biomedical applications like neural recording and stimulation, thanks to its enhanced biocompatibility and electronic properties. Drug delivery by PEDOT is typically achieved by incorporating drugs as dopants during the electrodeposition procedure and a subsequent release can be promoted by applying a cathodic trigger that reduces PEDOT while enabling the drug to diffuse. This approach has several disadvantages including, for instance, the release of contaminants mainly due to PEDOT decomposition during electrochemical release. Herein we describe a new strategy based on the formation of a chemical linkage between the drug and the conductive polymer. In particular, dexamethasone was successfully integrated into a new electropolymerized PEDOT–Dex composite, leading to a self‐adjusting drug release system based on a biochemically hydrolysable bond between dexamethasone and PEDOT. Abstract : Let's make it self‐releasing : For several years the delivery of bioactive molecules, including Dexamethasone, from conductive polymers has been based on the "ionic‐approach", which needs an external electrochemical trigger. Our new protocol, based on the chemical conjugation of Dexamethasone to the PEDOT backbone, enables a biochemically controlled release of Dexamethasone in response to the inflammation of the surrounding tissue.